Towards an Apex sharia court in Malaysia - Shuaib, Farid Sufian; Mohd Kamal, Mohd Hisham; Ahmad Bustami, Tajul Aris; Othman, Noraini; Sulaiman, Mohamad Syafiq (Universiti Putra Malaysia, 2017)
Malaysia has 14 Sharia court systems. The main reason for this state of affairs is the distribution of legislative powers under the Federal Constitution between the Federation and the states where Islam and Islamic law are state matters. This paper looks at the consequences of having several distinct Sharia court systems. The Sharia courts and the laws differ from one state to another. This paper looks at the legal possibility of having one apex court for all the 14 Sharia court systems to streamline the administration and decisions of the Sharia courts.